2018
DOI: 10.9734/jabb/2018/40699
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Toxicity & Biomarker Response to a Daily Dose of Toothpaste in Male Albino Rats

Abstract: This study was carried out to evaluate the biomarker response of male albino wistar rats (Rattus novergicus) to a daily dose of toothpaste. Twenty four wistar rats were divided randomly into two groups and housed in wooden cages. The first group which is the test group was administered in varying doses (250 ul, 270 ul, 300 ul) according to their body weight (0.00167 mg/g body weight) per week for three weeks while on the fourth week no treatment was administered. This was done to observe the rate of recuperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…[20] Another study observed that the sperm count was lower in the Ris and Halo groups than in the control group, while the percentage of morphology for viable sperm cells decreased significantly, and the percentage of debris increased. [21] In conjunction with the previous studies, [20,21] our results showed that while sperm motility decreased in Halo and Ris groups compared to the control group, the percentage of morphology for tail and total abnormality increased significantly and also the percentage of death sperm increased. There is no study in the literature on the semen quality of Arip and Quet.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…[20] Another study observed that the sperm count was lower in the Ris and Halo groups than in the control group, while the percentage of morphology for viable sperm cells decreased significantly, and the percentage of debris increased. [21] In conjunction with the previous studies, [20,21] our results showed that while sperm motility decreased in Halo and Ris groups compared to the control group, the percentage of morphology for tail and total abnormality increased significantly and also the percentage of death sperm increased. There is no study in the literature on the semen quality of Arip and Quet.…”
Section: Resultssupporting
confidence: 88%
“…However, it is known that increasing prolactin levels by drugs such as antipsychotics have been shown to cause an indirect decrease in sexual function because of decreasing testosterone levels. [21,26] In this study, prolactin level was not measured, but there is evidence that both Halo and Ris increased plasma prolactin levels in previous studies. [27,28] On the other hand, the results of previous studies support the view that increasing plasma prolactin due to both Ris and Halo also reduces testosterone levels, which is thought to cause a decrease in sexual function.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation